Vascular- and hepato-protective effects of passion fruit seed extract containing piceatannol in chronic high-fat diet-fed rats. Issue 9 (1st September 2016) - Ishihata, Akira; Maruki-Uchida, Hiroko; Gotoh, Nozomi; Kanno, Sumika; Aso, Yoshitaka; Togashi, Satoshi; Sai, Masahiko; Ito, Tatsuhiko; Katano, Yumi
Abstract : The effects of chronic administration of piceatannol-enriched (9.5% w/w) passion fruit seed extract (PFSE) on the cardiovascular damage induced in a high-fat (HF) diet-fed model of Fischer 344 rats were evaluated. Abstract : The effects of chronic administration of piceatannol-enriched (9.5% w/w) passion fruit seed extract (PFSE) on the cardiovascular damage induced in a high-fat (HF) diet-fed model of Fischer 344 rats were evaluated. Rats were fed the control, HF, or HF diets containing PFSE (0.5% w/w) for 16 weeks, and the effects of the various diets on the tissue weight, serum lipid profile, hepatic fibrosis, hepatic ductular reaction, cardiac function and aortic ring reactivity were examined. HF diet-fed rats developed signs of cardiovascular disease with abnormal serum profiles compared to control diet-fed rats. PFSE supplementation improved the liver hypertrophy and hepatic histology of the HF diet-fed rats. In addition, the triglyceride and cholesterol levels, platelet aggregation, cardiac function, and acetylcholine-mediated relaxation of the aortic ring were improved. These results suggest that the chronic intake of PFSE containing piceatannol prevents HF diet-induced cardiovascular disease in rats.